Three-Dimensional Unsteady Analysis of Fluid–Structure Interaction in Check Valves of Diaphragm Volumetric Pumps (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
A comprehensive unsteady three-dimensional numerical model employing dynamic meshing techniques has been developed to simulate the fluid–structure interaction (FSI) occurring within the non-return valves of air-operated diaphragm pumps. This advanced 3D CFD model offers a more precise representation of flow dynamics and a more accurate assessment of valve motion behavior compared to the earlier 2D model previously introduced by the authors. The improved model particularly enhances the understanding of internal volumetric losses caused by valve movement, which negatively impact the overall efficiency of the pump.The study investigated both piston-type and deformable diaphragm geometries under sinusoidal displacement conditions. Results showed comparable performance in terms of basic pump functionality for both configurations. Detailed simulations under normal operating and free-discharge conditions revealed increased instability in the check valves when the supplied air pressure was low.Notably, the exhaust valve exhibited significant valve "tapping," characterized by repeated partial closures during the forward stroke due to strong fluid–structure interactions. In contrast, the intake (aspirating) valve demonstrated more stable sealing behavior, with only minor reopening observed at the onset of the backward stroke.These numerical insights have proven valuable for pump manufacturers, informing improvements in valve design, material selection, and maintenance strategies. The findings have directly contributed to the development of new and more efficient pump prototypes